Pengembangan Destinasi Agrowisata di Desa Tipang dengan Memanfaatkan Kearifan Lokal Sebagai Daya Tarik Wisata Desa Tipang - Open Gerhard Siahaan; Immanuel Silaban (Journal of Social Interactions and Humanities, 2022)
This study aims to explain and find strategies and implementations of developing agro-tourism destinations in Tipang Village by utilizing local wisdom as a tourist attraction in Tipang Village. Tipang Village is one of the tourist areas located in Humbang Hasunduta Regency, known by tourists because it has the stunning natural beauty of Lake Toba and also a number of traditional Batak cultural sites. The location of the agro-tourism area of ​​Tipang Village is very potential to be developed because it is close to the panorama of Lake Toba, coupled with the many natural and cultural tourist attractions that lie within it, becoming a special attraction for tourists. This study uses a qualitative approach that seeks to explain phenomena based on field facts. Strategy and implementation of tourism ideas Development of agro-tourism destinations in Tipang Village by utilizing local wisdom as a tourist attraction in Tipang Village so that there is an increase in tourist visits and implementation of increasing tourism potentials that can be developed in Humbang Hasundutan Regency which is one of the potential agrotourism in North Sumatra.